Trombolisis Intra-arterial Perkutan pada Stroke Iskemik Peri-angiografi Koroner: Pengalaman Awal di Pusat Jantung Nasional Harapan Kita - Muhammad Fadil; Dicky Hanafy; I Irmalita; Doni Firman; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2010)
Background. Ischemic stroke is a rare but well-known complication of cardiac-catheter interventions attributable mostly to embolism. Peri-coronary angiography stroke, represents a unique opportunity for im-mediate stroke interventional therapy with intravenous, catheter based intra-arterial thrombolysis (IAT) or combined therapy using recombinant tissue plasminogen activator (rtPA). Intra-arterial thrombolysis is an option for treatment of selected patients who have major stroke of < 6 hours duration due to occlusion of the Media Cerebral artery(MCA) and who are not otherwise candidates for intravenous rtPA (Class I, Level of Evidence B, AHA guidelines). Objective.To review the first experience of percutaneous intra-arterial thrombolysis(PIAT) as a management of acute ischemic stroke due to complication of coronary angiography procedure. Summary. We present 3 cases of acute ischemic stroke which happened during coronary angiography procedures. All of them (NIHSS 30, 20 and 34) were treated immediately with intra-arterial thrombolysis (IAT) recom-binant tissue Plasminogen Activator (rtPA) and had a very good outcome with no residual of stroke (NIHSS 0). Although it has been stated clearly in the AHA guidelines for the early management of adult with ischemic stroke, up until now the procedure of IAT or (intra-venous thrombolysis) IVT upon acute ischemic stroke is not established yet in standard operational procedure of National Cardiovascular Center Harapan Kita (NCCHK) Jakarta, which perhaps makes the physicians hesitate on performing these procedures due to legal aspects, while in the other hand the risks of acute ischemic stroke remain the potential threats on every single coronary angiography or any intensive catheter based procedures.